Iodothiophenes and Related Compounds as Coupling Partners in Copper-Mediated N-Arylation of Anilines - Bouarfa, Salima; Bentabed-Ababsa, Ghenia; Erb, William; Picot, Laurent; Thiéry, Valérie; Roisnel, Thierry; Dorcet, Vincent; Mongin, Florence (Synthesis, 2020)
N-Arylation of various 2-acylated anilines with different electron-rich heteroaryl iodides (2- and 3-iodothiophenes, 2- and 3-iodobenzothiophenes, 2-iodobenzofuran) was achieved by using activated copper and potassium carbonate in dibutyl ether at reflux. The reactivity of the different heteroaryl iodides and anilines employed was discussed and rationalized on the basis of their electronic features. Subsequent cyclization by aromatic electrophilic substitution easily took place in the case of C2-free (benzo)thienyl or C3-free (benzo)furyl derivatives, affording original tri- and tetracycles. The antiproliferative activity of most of them was evaluated in A2058 melanoma cells and revealed four chlorinated tetracycles as effective growth inhibitors.
Keywords: Key words; aniline; thiophene; iodine; N-arylation; copper; antiproliferative activity; melanoma cells